Identification of double-stranded genomic DNA spanning all chromosomes with mutated KRAS and p53 DNA in the serum exosomes of patients with pancreatic cancer - Kahlert, Christoph; Melo, Sonia A.; Protopopov, Alexei; Tang, Jiabin; Seth, Sahil; Koch, Moritz; Zhang, Jianhua; Weitz, Jürgen; Chin, Lynda; Futreal, Andrew; Kalluri, Raghu (The journal of biological chemistry, 2014)
Exosomes are small vesicles (50-150 nm) of endocytic origin that are released by many different cell types. Exosomes in the tumor microenvironment may play a key role in facilitating cell-cell communication. Exosomes are reported to predominantly contain RNA and proteins. In this study, we investigated whether exosomes from pancreatic cancer cells and serum from patients with pancreatic ductal adenocarcinoma contain genomic DNA. Our results provide evidence that exosomes contain >10-kb fragments of double-stranded genomic DNA. Mutations in KRAS and p53 can be detected using genomic DNA from exosomes derived from pancreatic cancer cell lines and serum from patients with pancreatic cancer. In addition, using whole genome sequencing, we demonstrate that serum exosomes from patients with pancreatic cancer contain genomic DNA spanning all chromosomes. These results indicate that serum-derived exosomes can be used to determine genomic DNA mutations for cancer prediction, treatment, and therapy resistance.
Gesehen am 30.09.2020